Statsborgerskabets materialiseringer - Damsholt, Tine (Tidsskrift for kulturforskning, 2008)
Citizenship ceremonies are a solution that many old nation-states resort to when facing the multicultural challenge at the turn of the 21st century. Some countries continue to practice older traditions, whereas other countries have newly invented traditions celebrating naturalization and citizenship. In this article, Great Britain, Sweden, Norway and Denmark will serve as examples of the latter. In a performative approach the ethnography of how citizenship is carried out at the ceremonies is elaborated. At the ceremonies citizenship is not only enacted in different discourses. The scope of the article is to show how citizenship is materialized in different versions of bodily practice, soundscapes, and in objects like flags, certificates, pins, medals, food and beverage. Both human and non-human actors are engaged in the citizenship ceremony, along with absent, present, and historical forms and practices. Thus the complexity, multiplicity, and heterogeneity of citizenship is emphasised as is citizenship as emergent ontologies in practice.